Evaluasi Kinerja Infrastruktur Pengelolaan Sampah Di Pusat Kota Garut - Adi Susetyaningsih; Thoriq Awalludin (Jurnal Konstruksi, 2026)
Urban waste management problems continue to increase along with population growth and community activities. The high volume of waste generation is not proportional to the availability of waste transportation fleets and the condition of Temporary Disposal Sites (TPS), most of which still operate conventionally, resulting in waste accumulation at TPS locations and increasing the burden on Final Disposal Sites (TPA). This study aims to evaluate the performance of the existing waste transportation fleet and analyze the planning of segregated TPS facilities as a strategy to reduce the volume of waste sent to the TPA. The research method used is descriptive quantitative, with data collected through field observations and documentation from related agencies. Data were analyzed by calculating waste generation and composition, evaluating fleet adequacy based on capacity, hauling frequency, and technical conditions, and designing segregated TPS facilities adapted to the characteristics of urban waste. Based on the analysis results, waste generation in Garut Kota District reaches approximately 57.28 tons per day, with an average transportation distance of approximately 11 km to the Pasirbajing TPA. The ideal number of fleets required to handle the total waste generation consists of 9 dump trucks and 5 arm roll trucks, while the existing condition only fulfills around 70% of the ideal requirement. The analysis was also complemented by transportation route planning to improve daily hauling efficiency. The novelty of this research lies in the integration of fleet evaluation and segregated TPS planning, which have generally been studied separately in previous research. The results of this study are expected to provide technical recommendations in the form of fleet addition and rejuvenation, hauling optimization, segregated TPS development, and the establishment of effective transportation routes. Therefore, this study is expected to support the improvement of a waste management system that is more efficient, sustainable, and adaptive to urban needs.